Multi-point laser coherent detection system and its application on vibration measurement - Fu, Y. (2018)
Laser Doppler vibrometry (LDV) is a well-known interferometric technique to measure the motions, vibrations and mode shapes of machine components and structures. The drawback of commercial LDV is that it can only offer a pointwise measurement. In order to build up a vibrometric image, a scanning device is normally adopted to scan the laser point in two spatial axes. These scanning laser Doppler vibrometers (SLDV) assume that the measurement conditions remain invariant while multiple and identical, sequential measurements are performed. This assumption makes SLDVs impractical to do measurement on transient events. In this paper, we introduce a new multiple-point laser coherent detection system based on spatial-encoding technology and fiber configuration. A simultaneous vibration measurement on multiple points is realized using a single photodetector. A prototype16-point laser coherent detection system is built and it is applied to measure the vibration of various objects, such as body of a car or a motorcycle when engine is on and under shock tests. The results show the prospect of multi-point laser coherent detection system in the area of nondestructive test and precise dynamic measurement.